The man and the family: Their marriage and political-social organization in Q'ero - Núñez del Prado, Óscar (1969)
The expedition had to be integrated almost entirely by specialists from the National University of Cuzco, and that is how it left this city, with the following personnel: A Geographer, Dr. Marino Escobar Moscoso. A Folklorist, Doctor Efraín Morote Best; An Archaeologist, Dcotor Manuel Chávez Ballón; A Musicologist, Mr. Josafat Roel Pineda; An Archeology Assistant, Mr. Luis Barreda Murillo; A Folklore Assistant, Mr. Demetrio Roca; A Photographer, Mr. Malcolm K. Burke; An editor of "La Prensa", Mr. Demetrio Tupac Yupanqui; A Social Anthropologist, Head of the Expedition, who speaks to you.